The pharmacokinetics of antibiotics in cystic fibrosis - Akkerman-Nijland, Anne M.; Akkerman, Onno W.; Grasmeijer, Floris; Hagedoorn, Paul; Frijlink, Henderik. W.; Rottier, Bart. L.; Koppelman, Gerard. H.; Touw, Daniel. J. (Expert opinion on drug metabolism & toxicology, 2021)
Dosing of antibiotics in people with cystic fibrosis (CF) is challenging, due to altered pharmacokinetics, difficulty of lung tissue penetration, and increasing presence of antimicrobial resistance. The purpose of this work is to critically review original data as well as previous reviews and guidelines on pharmacokinetics of systemic and inhaled antibiotics in CF, with the aim to propose strategies for optimization of antibacterial therapy in both children and adults with CF. For systemic antibiotics, absorption is comparable in CF patients and non-CF controls. The volume of distribution (Vd) of most antibiotics is similar between people with CF with normal body composition and healthy individuals. However, there are a few exceptions, like cefotiam and tobramycin. Many antibiotic class-dependent changes in drug metabolism and excretion are reported, with an increased total body clearance for ß-lactam antibiotics, aminoglycosides, fluoroquinolones, and trimethoprim. We, therefore, recommend following class-specific guidelines for CF, mostly resulting in higher dosages per kg bodyweight in CF compared to non-CF controls. Higher local antibiotic concentrations in the airways can be obtained by inhalation therapy, with which eradication of bacteria may be achieved while minimizing systemic exposure and risk of toxicity.